Safety certification of improved biomass cooking stoves—A test method for tipping, sliding, and spilling stability - Zhao, Nan; Zhang, Yixiang; Li, Xin; Kimemia, David K.; Annegarn, Harold J.; Makonese, Tafadzwa; Dong, Renjie; Zhou, Yuguang (Frontiers in Energy Research, 2023)
Usage of inefficient and unsafe cookstoves is a cause of significant health losses and injuries in low-income communities. Efforts to develop and disseminate clean cookstoves have concentrated on optimizing thermal and emissions performance, but minimal attention was given to safety aspects. Discussions conducted by the ISO TC285 Technical Committee are ongoing on the derivation of universal biomass cooking stove standard that aims to guide the development and marketing of products that are safe, efficient with clean burning. Under this, cooking stove safety guidelines addressing a range of hazards have been issued to the community of practice. This work critically addressed the current guideline on cooking stove stability by pointing out the inadequacy of the test and suggesting extra tests for an improved rating of a candidate stove. With pot and fuel introduced to the research, there may be three different failure modes for various pot and stove combinations, which were tipping, sliding or spilling. The tests were conducted on an inexpensive purposely-built “tiltometer” that allowed testing the angles for stove tipping and sliding, as well as cooking pot sliding and spilling failure. The results indicated that tipping angles for a selected list of modern stoves varied widely based on different shapes and masses, from 27° to 73°. Also, the performance of three different failure modes would place the same stove in different tiers by the current safety protocol. Theoretical geometric calculations for the tipping angle were conducted and the relative errors were within 2.9% to 12.7% for three different orientations. It is suggested a revision of the interim stove safety standard should be promoted to incorporate the findings of this study.